2017
DOI: 10.1111/jphp.12792
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial synergism and cytotoxic properties of Citrus limon L., Piper nigrum L. and Melaleuca alternifolia (Maiden and Betche) Cheel essential oils

Abstract: The results of this study encourage use of tested EOs in development of a novel agent intended for prevention or therapy of corresponding oral disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 38 publications
2
23
1
5
Order By: Relevance
“…On the other hand, fungi strains of A. niger and S. cerevaceae were found to display moderate activity with the zone of 9 mm. The present results are higher than reported data (Bag & Chattopadhyay, ; Nikolic et al, ) whereas, some oils were reported to have higher activity (Morsy & El‐Salam, ; Singh et al, ). This variation is due to the major component present in the oils.…”
Section: Resultscontrasting
confidence: 91%
See 1 more Smart Citation
“…On the other hand, fungi strains of A. niger and S. cerevaceae were found to display moderate activity with the zone of 9 mm. The present results are higher than reported data (Bag & Chattopadhyay, ; Nikolic et al, ) whereas, some oils were reported to have higher activity (Morsy & El‐Salam, ; Singh et al, ). This variation is due to the major component present in the oils.…”
Section: Resultscontrasting
confidence: 91%
“…Moreover, Krishnaraju et al () reported the LC 50 30 μg/mL at the dose of 1–5000 μg/mL. In another report, the LC 50 values were found to have 25.57–56.74 μg/mL on the cell line assay (Nikolic et al, ). The observed difference may be due to the chemical composition of the oils as well as synergistic action.…”
Section: Resultsmentioning
confidence: 97%
“…The product should not cause death of the cells, nor affect their cellular functions, as was observed in this work. Nicolic et al studied the cytotoxic activity of lemon essential oil ( Citrus limon L.) using the human fetal lung fibroblast cell line derived from the test of 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium (MTT) and confirmed the absence of cytotoxic activity, which agrees with the results obtained in the present work.…”
Section: Resultssupporting
confidence: 90%
“…Among the analysed metabolites, sabinene, β-myrcene, δ-3-carene, γ-terpinene, limonene, α-capaene, octanoic acid, and isocaryophillene were reported to have antimicrobial properties. [14][15][16][17][18][19] Identified metabolites reported to have antimicrobial and antioxidant properties are also tabulated in Table 5. Figure 4A).…”
Section: Gc-ms Analysis Of Eomentioning
confidence: 99%